Experimental and theoretical Raman study on the structure and microstructure of Li0.30La0.57TiO3 electrolyte prepared by the sol-gel method in acetic medium. Issue 14 (1st November 2016) - Romero, Mariano; Faccio, Ricardo; Vázquez, Santiago; Davyt, Sebastián; Mombrú, Álvaro W.
Abstract: In this report, we prepare LLTO ceramics by the sol-gel method in acetic medium. Raman spectroscopy showed the formation of lanthanum and titanium acetates precursors, which after calcination, lead to formation of the LLTO nanoparticles. Raman spectra were scanned directly over the LLTO pellets and the disappearance of impurities was observed during the microstructure evolution with increasing sintering temperature. X-ray diffraction characterization, including full pattern profile fitting refinements, showed no drastic changes in the unit cell parameters of the LLTO perovskite, but a large increase in the crystallite size domain was observed with increasing sintering temperature. Additionally, an interesting structural phase transition for the Li0.30 La0.57 TiO3 perovskite structure was observed, from tetragonal P4/mmm to distorted-cubic Pm-3m spacegroup, for the highest sintering temperature (Ts=1300 °C). Experimental and theoretical simulations of Raman spectroscopy confirmed the formation of a distorted-cubic phase and confocal Raman spectroscopy showed the presence of traces of impurities at the grain boundary region. In spite of the low total lithium conductivity observed, the electrochemical impedance spectroscopy analysis showed a remarkable increase in the lithium bulk conductivity for Ts=1300 °C. This fact could be attributed to the structural phase transition from tetragonal to the cubic crystal system.